The Slow Conquest of the Argentine Frontier: From the Subversive Gaucho through the Erasure of First Peoples to the Cold War Military Triumph over Antarctica - Sheinin, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
This article assesses the shifting character of the Argentine frontier. Over time, Argentines have altered their understanding of the concept of a frontier. Two constants over the past century and a half, however, have been the popular notion of the conquest of Indigenous peoples as balefully incomplete, and the associated idea of a racially compromised frontier. These have contrasted sharply with settler myths of the destruction of First Peoples as a steppingstone to early nation building. During the mid-twentieth century, the influence of US American cowboy culture helped confirm the erasure of Indigenous Argentines in popular culture. At the same time, there was a southward shift of the imagined frontier in cultural, territorial, and military claims to Malvinas and Antarctica, territories that, unlike northern Argentine provinces, held no Indigenous populations.